2013
DOI: 10.7150/ijms.4875
|View full text |Cite
|
Sign up to set email alerts
|

Oral High-Dose Ankaferd Administration Effects on Gastrointestinal System

Abstract: Background and aims: Ankaferd Blood Stopper (ABS) is a herbal extract obtained from five different plants. It has a therapeutic potential for the management of external hemorrhage and controlling gastrointestinal bleeding. However, ABS's effects are not unknown on gastrointestinal systems. The aim of this study was to assess the effect of short- and long-term systemic exposure and gastrointestinal safety following the oral administration of high-dose ABS in rats.Methods: Eighteen healthy adult male rats were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…Acute toxicity was not observed in rats given ABS at this dose. Similarly, no signs of serious toxicity were reported in rats with use of 4 ml/kg dose of ABS for 3 months [14]. In our study, it was shown that short-term administration of a high dose of ABS was able to control hemorrhagic lesions with no associated serious systemic toxicity.…”
Section: Conflict Of Interestsupporting
confidence: 50%
See 1 more Smart Citation
“…Acute toxicity was not observed in rats given ABS at this dose. Similarly, no signs of serious toxicity were reported in rats with use of 4 ml/kg dose of ABS for 3 months [14]. In our study, it was shown that short-term administration of a high dose of ABS was able to control hemorrhagic lesions with no associated serious systemic toxicity.…”
Section: Conflict Of Interestsupporting
confidence: 50%
“…In vitro data demonstrating beneficial antibacterial and wound healing profile of ABS supported its use in the control of gastrointestinal [7][8][9][10][11] and mediastinal bleeding [12,13]. In a study by Akbal et al, it was emphasized that the administration of ABS as a single dose for gastrointestinal system bleeding did not cause systemic side effects but care should be taken when it's used for longer term (e.g., for 3 months) [14]. In experimental esophagitis models, administration of ABS was shown to provide marked improvement in mortality and stenosis index [15].…”
Section: Introductionmentioning
confidence: 97%
“…Another difference of this patient in comparison with other cases presented in the medical literature is the oral use of ABS. In only a few recent studies have high doses of oral ABS been reported to be safe in healthy rats (13) and tandem oral, rectal, and nasal administrations in patients with Klatskin tumor (14). Although this patient may contribute to the medical community in showing the safety and efficacy of systemic (oral) ABS in patients with disorders of hemostasis, it is obvious that further experience on its use in patients and further clinical studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Poly­(ethylene oxide) (PEO) is a synthetic hydrophilic and biocompatible polymer similar to polyethylene glycol (PEG) but with a larger molecular weight (>100 kDa). It occurs as a free-flowing white powder which has been approved by the FDA for use as an excipient to increase viscosity and modify the flow of aqueous solutions. Recently, ultrahigh molecular weight (UHMW) PEO (viscometric average MW 1700 kDa) has been found to be an effective hemostatic agent for use in the treatment of gastrointestinal bleeding. This is because when PEO powder is applied to a wound site, it rapidly facilitates production of a gel-like matrix incorporating platelets, red blood cells, and coagulation proteins that can seal the bleeding tissue. ,, UHMW PEO is superior to traditional absorbable polysaccharide particles in being nonbiodegradable and insensitive to pH which greatly reduces the risk of a rebleed. However, questions remain as to whether UHMW PEO undergoes systemic absorption from the wound site and, if so, whether it is excreted unchanged or in the form of metabolites.…”
mentioning
confidence: 99%
“…4−7 This is because when PEO powder is applied to a wound site, it rapidly facilitates production of a gel-like matrix incorporating platelets, red blood cells, and coagulation proteins that can seal the bleeding tissue. 4,8,9 UHMW PEO is superior to traditional absorbable polysaccharide particles in being nonbiodegradable and insensitive to pH which greatly reduces the risk of a rebleed. However, questions remain as to whether UHMW PEO undergoes systemic absorption from the wound site and, if so, whether it is excreted unchanged or in the form of metabolites.…”
mentioning
confidence: 99%